Subclinical deafness among medical students using ear phones - PRAKASH MANOHARAN; HARI P.M; PAVITHRA SAIKUMAR; GUNAVATHY K; KARTHIK KUMAR M (International Journal of Pharma and Bio Sciences, 2017)
Sensorineural hearing loss (SNHL) is due to defects either in the sensory end organ of the cochlea or in neural transmission to the central nervous system (CNS). A defect exists either in the conversion of acoustic energy by the sense organ of the inner ear or in the transmission of neural impulses centrally. Noise induced hearing loss is the second most common cause of SNHL after presbycusis. Both the intensity and the duration of noise exposure interact to influence potential damage to the hair cells of the inner ear for which no medical or surgical treatment is known. The aim of this study is to estimate the prevalence of subclinical noise induced hearing loss due to ear phone usage among medical students.. Extensive usage of ear phones can cause damage to the outer hair cells and hence it can cause irreversible sensorineural hearing loss among people within few years. This adds to the hearing loss which is incurred by the increasing environmental sounds and such people are more prone for disabling deafness later on in life due to presbyacusis. A cross sectional study was conducted in a group of students of age 19-23years in which the participants were selected based on certain inclusion and exclusion criteria. Eligible participants were given a questionnaire about the usage of ear phones like duration of ear phone usage, number of hours /day, model of ear phone, volume level etc and were subjected to pure tone audiometry test for finding Bone conduction pure tone average. The data was analysed statistically. It showed that 28% showed minimal subclinical sensorineural hearing loss and with > 2yrs usage of ear phones the SNHL was found to be 40%.It was noticed that there is a marked increase in SNHL among ear phone users in noisy environment.